1988
DOI: 10.1210/endo-122-4-1689
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Desensitization Preferentially Inhibits Expression of the Luteinizing Hormone β-Subunit Genein Vivo

Abstract: In this study we investigated changes in steady state cytoplasmic mRNA levels for LH subunits in pituitaries of male rats desensitized by continuous infusion of GnRH in vivo. Seven days of GnRH infusion (340 micrograms/day) reduced (P less than 0.01) LH beta mRNA levels in intact adult male rats and prevented the LH beta mRNA rise observed after castration. In contrast, common alpha mRNA doubled (P less than 0.05) in intact rats, and the elevated alpha mRNA after 7 days castration was unchanged. Serum and pitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
0
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 0 publications
8
21
0
2
Order By: Relevance
“…Prior to OVX, se rum LH concentrations and pituitary LH contents were similar between these two age groups, while the LHp mRNA expression was significantly lower in middle-aged PE rats. From these data it would appear that LHp mRNA expression is tonically decreased in PE rats, and similar findings have been recently reported in studies on aged fe male rats [17], Hypothalamic secretion o f gonadotropin releasing hormone has been shown to be important in regulating pituitary LHp mRNA expression in which pul satile administration is required [18][19][20][21], Several lines o f evidence have suggested that in middle-aged PE rats, hy pothalamic gonadotropin-releasing hormone pulse fre quency and amplitude are decreased [22,23], and the present findings demonstrating low LHp mRNA expres sion in PE rats would be compatible with this hypothesis. Previous studies have characterized the cyclic changes in pituitary LHp mRNA expression during the estrous cycle, with increased expression beginning early on proestrus afternoon [24], In the present study, the pituitary LHP mRNA expression in young rats at 12.00 h on proestrus (day 0) was significantly greater than that in middle-aged PE females.…”
Section: Discussionsupporting
confidence: 86%
“…Prior to OVX, se rum LH concentrations and pituitary LH contents were similar between these two age groups, while the LHp mRNA expression was significantly lower in middle-aged PE rats. From these data it would appear that LHp mRNA expression is tonically decreased in PE rats, and similar findings have been recently reported in studies on aged fe male rats [17], Hypothalamic secretion o f gonadotropin releasing hormone has been shown to be important in regulating pituitary LHp mRNA expression in which pul satile administration is required [18][19][20][21], Several lines o f evidence have suggested that in middle-aged PE rats, hy pothalamic gonadotropin-releasing hormone pulse fre quency and amplitude are decreased [22,23], and the present findings demonstrating low LHp mRNA expres sion in PE rats would be compatible with this hypothesis. Previous studies have characterized the cyclic changes in pituitary LHp mRNA expression during the estrous cycle, with increased expression beginning early on proestrus afternoon [24], In the present study, the pituitary LHP mRNA expression in young rats at 12.00 h on proestrus (day 0) was significantly greater than that in middle-aged PE females.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, sustained GnRH causes a more or less rapid depletion of both FSHβ and LHβ mRNA due to transcription arrest associated with transcript degradation. Contrasting with β-counterparts, the α-subunit mRNA levels remain essentially constant or even increases slightly for days [8][9][10]. These observations are consistent with current clinical studies showing that long-term administration of GnRH superagonists readily induced depletion of LH and FSH but increased free α-subunit levels in the serum of treated patients [11].…”
Section: Introductionsupporting
confidence: 88%
“…Indeed, low frequencies in the range one stimulus every two or four hours appear to preferentially increase FSHβ mRNA levels whereas higher frequencies preferentially stimulate LHβ and α subunit mRNA [13,14]. In vivo, permanent exposure to GnRH leads to a more or less rapid depletion of both FSHβ and LHβ mRNA in a manner that suggests a rapid transcription arrest followed by RNA degradation, while the α-subunit mRNA [15][16][17]. The latter data are consistent with current clinical studies showing that long-term administration of GnRH superagonists induces depletion of LH and FSH but increases free α-subunit levels in the serum of treated patients [18].…”
Section: Gnrh Is Crucial For Regulated Expression Of Gonadotropin Submentioning
confidence: 99%